Faithful Passion and its Impact on da’wah, the Believer of the Aal- Pharaoh, and the Believer of the Aal- Yass as a model - mahmoud, muayid; Thamel , Hazem (Islamic Sciences Journal, 2023)
ABSTRACT The subject of the faithful emotion is one of the important topics mentioned in the Qur’anic stories, as it expresses the most important types of human emotions, and an important part of the components of the human entity. This study aims to indicate some of the sides and people who represent this emotion ,i.e. the emtion of the believer of Aal-pharaoh and the emotion of the believer of Al Yassin, in addition to explaining the impact of these emotions on these sincere advocacy models and their impact on the recipients, so that it would be a sound approach for everyone who followed the path of the prophets in conveying the word of truth, and the call to Allah Almighty, and in what achieves human happiness in this life and the hereafter, without cariy about the loss of money, prestige, position, or even the loss of the soul that he may suffer, because this passion transcends its owner above all the adornments of this world and its fleeting adornment, in order to achieve the goals of true faith.